Dukungan Mental dan Psikososial pada Remaja dengan Orang Tua Broken Home - Indari; Dian Pitaloka Priasmoro; Efti Dio Fatma; Vera Puspita (Yayasan Inspirasi El Burhani, 2022)
Introduction: Broken home families are an unfavorable condition and can cause disruption of adolescent development and can lead to juvenile delinquency and psychological disorders such as stress, anxiety, and depression. This phenomenon can certainly have a detrimental impact on adolescents if not treated immediately. Objective: The potential for mental health problems or juvenile delinquency will increase if no efforts are made. The provision of mental health and psychosocial support to adolescents who experience a broken home is expected to provide an intervention so that adolescents do not experience health problems, especially in their mental state. Method: The method used in this service is the first to conduct mental health screening on broken home adolescents using SRQ 29, then the service team provides education about broken homes and education about psychosocial disorders in adolescents. The next stage is that the youth and the team carry out Mind fullness Sharia Islam (MSI). Service activities were carried out using Zoom meetings due to the Covid 19 Pandemic conditions. The last activity carried out was to evaluate the emotional mental health of adolescents using SRQ 29. Results: The results of the screening with SRQ showed that 21 adolescents experienced psychosocial disorders, namely 13 adolescents experienced anxiety, 7 adolescents experienced PTSD and one teenager experienced drugs. After educating and giving MSI, adolescents understand about broken homes and additions, characteristics of psychosocial disorders and have strengths after MSI is done. Conclusion: Based on the results above, it is hoped that support for broken home teenagers can be given with positive activities and appropriate interventions.